Effect of humidity and temperature on the potential‐induced degradation. (15th August 2012) - Hoffmann, Stephan; Koehl, Michael
ABSTRACT This paper focusses on the physical conditions for a degradation mechanism of photovoltaic modules, known as potential‐induced degradation. The analysis was made on several levels. At first, the influence of humidity and temperature on the potential‐induced leakage current has been investigated, the second step consists of an accelerated test scheme in a climatic chamber and the third one is outdoor exposure with high voltage stress in two different climate regions. The humidity has a huge impact on the leakage current. Therefore, a test in the climate chamber accelerates the stress found in the field of some orders of magnitude. Copyright © 2012 John Wiley & Sons, Ltd.